Phase 2 trial with imeglimin in patients with Type 2 diabetes indicates effects on insulin secretion and sensitivity. Issue 6 (14th October 2022) - Theurey, Pierre; Thang, Carole; Pirags, Valdis; Mari, Andrea; Pacini, Giovanni; Bolze, Sébastien; Hallakou‐Bozec, Sophie; Fouqueray, Pascale
Abstract: Introduction: The aim of the present study was to evaluate the effect of 18‐week monotherapy with imeglimin on glucose tolerance and on insulin secretion/sensitivity in type 2 diabetic (T2D) patients. Methods: The study was an 18‐week, double‐blind clinical trial in T2D subjects previously treated with stable metformin therapy and washed out for 4 weeks. Subjects were randomized 1:1 to receive a 1500 mg bid of imeglimin or placebo. The primary endpoint was the effect of imeglimin vs placebo on changes from baseline to week 18 in glucose tolerance (glucose area under the curve [AUC]) during a 3 h‐glucose tolerance test [OGTT]). Secondary endpoints included glycaemic control and calculated indices of insulin secretion and sensitivity. Results: A total of 59 subjects were randomized, 30 receiving imeglimin and 29 receiving placebo. The study met its primary endpoint. Least squares (LS) mean difference between treatment groups (imeglimin ‐ placebo) for AUC glucose from baseline to week 18 was −429.6 mmol/L·min ( p  = .001). Two‐hour post‐dose fasting plasma glucose was significantly decreased with LS mean differences of −1.22 mmol/L ( p  = .022) and HbA1c was improved with LS mean differences of −0.62% ( p  = .013). The AUC0‐180min ratio C‐peptide/glucose [LS mean differences of 0.041 nmol/mmol ( p  < .001)] and insulinogenic index were significantly increased by imeglimin treatment. The increase in insulin secretion was associated with an increase in beta‐cell glucose sensitivity. Additionally, the insulin sensitivity indices derived from the OGTT Stumvoll ( p  = .001) and Matsuda (not significant) were improved in the imeglimin group vs placebo. Imeglimin was well tolerated with 26.7% of subjects presenting at least one treatment‐emergent adverse event versus 58.6% of subjects in the placebo group. Conclusions: Results are consistent with a mode of action involving insulin secretion as well as improved insulin sensitivity and further support the potential for imeglimin to improve healthcare in T2D patients. Abstract : This article describes the results of a 18‐week double‐blind clinical trial, assessing the effects of imeglimin on insulin secretion and sensitivity using an oral glucose tolerance test in Caucasian Type 2 Diabetic patients. It reports for the first time the effect of imeglimin on dynamic insulin sensitivity and on insulin secretion using a sophisticated mathematical approach.